2019
DOI: 10.1182/blood-2019-129865
|View full text |Cite
|
Sign up to set email alerts
|

Pozelimab, a Human Antibody Against Complement Factor C5, Demonstrates Robust Inhibition of Alternative Complement Activity Both in Normal Human Serum and in Phase I Normal Healthy Volunteers

Abstract: INTRODUCTION: Blockade of complement factor C5 has demonstrated benefit in paroxysmal nocturnal hemoglobinuria, atypical hemolytic uremic syndrome, generalized myasthenia gravis and neuromyelitis optica. We have completed a Phase I study of pozelimab, a fully human anti-C5 IgG4, in healthy volunteers. Pozelimab was well tolerated and resulted in dose-dependent inhibition of hemolytic activity through the classical complement pathway in normal healthy volunteers. Complete inhibition of hemolytic activity was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This fully humanized antibody against C5 has been shown to suppress C5 levels and hemolysis in human serum and mice models in a more potent manner compared to eculizumab and ravulizumab ( 154 , 155 ). In a Phase 1 study in healthy subjects, pozelimab also showed 70% bioavailability after subcutaneous administration, allowing for more versatile administration options, such as weekly subcutaneous 400 mg administrations after a 15 mg/kg intravenous loading dose ( 156 ).…”
Section: Terminal Complement Pathway-targeting Treatments Of Inflammamentioning
confidence: 99%
“…This fully humanized antibody against C5 has been shown to suppress C5 levels and hemolysis in human serum and mice models in a more potent manner compared to eculizumab and ravulizumab ( 154 , 155 ). In a Phase 1 study in healthy subjects, pozelimab also showed 70% bioavailability after subcutaneous administration, allowing for more versatile administration options, such as weekly subcutaneous 400 mg administrations after a 15 mg/kg intravenous loading dose ( 156 ).…”
Section: Terminal Complement Pathway-targeting Treatments Of Inflammamentioning
confidence: 99%
“…Pozelimab, a fully human monoclonal immunoglobulin G4P (IgG4P) antibody directed against C5, has been trialled in healthy volunteers has demonstrated complement inhibition with a reduction in the complement function assay CH50 and a favourable safety profile. 35 Zilucopan, a daily SC injection showed promising results; however, the company have been taken over and looks to not be pursing PNH as a disease area of interest. 37 Similarly, nomacopan, a daily SC injection for PNH, presented at the 23rd European congress of haematology in 2018, showed a reduction in LDH and was well tolerated by eight patients, although it is no longer being developed by the company for PNH.…”
Section: Other C5 Inhibitorsmentioning
confidence: 99%
“… 77 Tesidolumab is a monoclonal antibody under development in a proof-of-concept phase 2 study in untreated patients with PNH; preliminary results are not yet available. 73 , 83 Pozelimab is a monoclonal antibody that demonstrated complement inhibition in healthy volunteers, 93 and an open-label, single-arm, phase 2 study is ongoing in patients with PNH who are either complement-inhibitor-naïve or have not recently received a complement inhibitor. 84 Zilucopan is a synthetic macrocyclic peptide inhibitor of complement C5.…”
Section: Management Of Pnh and The Impact Of C5 Inhibitorsmentioning
confidence: 99%